Canada: Schwatka's Franklin-Search Expedition, Starvation Cove - Klutschak, Heinrich (1889)
Starvation Cove. Most southern point known to have been reached by the retreating crews of Sir John Franklin's ill fated Expedition. http://members.eunet.at/castaway/history/history.html#Schwatka'sche%20Franklin-Aufsuchungs-Expedition